CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF GASTRITIS IN EVENKIA SCHOOLCHILDREN OF ETHNIC POPULATIONS - V. T. Manchuk (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents the data on the prevalence and clinical and. morphological characteristics of gastritis in Evenkia children. We examined. 299 native children — the Evenks (the Mongoloids) and. 1204 alien children (the Caucasians) of 7—17 years. We found, the increase of gastritis prevalence and. its progressive course in the Caucasians. In both ethnic populations we marked, the association, of gastritis with. Helicobacter fylori. At the same time erosive-ulcer lesions of mucous tunic in gastroduodenal area was diagnosed, in the Evenks two times less frequent than in the Caucasians. Besides, the infection in the Evenks was accompanied, by weaker stage of gastritis activity.